Soft materials nanoarchitectonics: liquid crystals, polymers, gels, biomaterials, and others - Katsuhiko Ariga (Beilstein Journal of Nanotechnology)
The concept of nanoarchitecture, as a post-nanotechnology methodology, can be defined as the construction of functional materials from nanometer-sized units using a variety of materials processes. It is believed to be particularly well suited to the assembly of soft materials that exhibit flexible and diverse structures and properties. To demonstrate its effectiveness, this review takes typical soft materials, including liquid crystals, polymers, gels, and biological materials, as examples. The aims are to extract the properties that emerge from them and to highlight the challenges that lie ahead. The examples also illustrate the potential applications, including organic semiconductor devices, electrochemical catalysts, thin-film sensors, solar energy generation, plastic crystal electrolytes, microactuators, smart light-responsive materials, self-repairing materials, enzyme cascade sensors, healing materials for diabetic bone defects, and bactericidal materials. As can be seen from these examples, soft materials nanoarchitectonics offers a wide range of material designs, specific functions, and potential applications. In addition, this review examines the current state and future of soft materials nanoarchitectonics. As an overall conclusion, it is highly anticipated that soft materials nanoarchitectonics will continue to develop significantly in the future.